AGE CONCEPT IN PHRASEOLOGICAL UNITS (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
The article aims to explore the phraseological units across different languages that pertain to the concept of age, examining how these expressions reflect cultural and societal attitudes towards various life stages, from youth to old age